ECONOMICS OF COMMON CONSUMPTION: FEATURES OF FUNCTIONING AND DEVELOPMENT PROSPECTS - Диха, Марія Василівна; Полозова, Валентина; Вороніна , Ірина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The essence of sharing is defined; the main factors of formation and development of the economy of shared consumption are characterized: the spread of advanced digital platforms and devices; economic rationality; new consumer needs; social transformations. The main advantages of business models of the sharing economy, the impact of sharing business models on the traditional development of economic sectors of individual states and the development of economies in the global dimension are highlighted. The main areas of the consumer economy in the world (transport services, rental housing, domestic services, professional services, co-financing), which are distributed through different platforms, are considered.(Uber, UberX, Lyft, Avtoshare, Relay Rides, Zimride, BlaBlaCar, Boston’s Hubway чи Chicago’s Divvy Bikes, Airbnb, HomeAway, Ebay, Amazon, OLX, TaskRabbit, Kabanchik, Sorted, Freelance, Bringwasmit, Etsy, Crafta, P2PU, Skillshare, Sharing academy Coursera, Khanacademy, Udemy, Wingly, Shareyourmeal, EatWith, Share city, Meal Sharing, VizEat, Happy Tree, Fixura, Lending Club, LendingClub, Zopa, Indiegogo, Gofundme, CircleUp, Friendsurance, InsPeer). The main sectors of development of the consumer economy in Ukraine and trends in the development of sharing platforms are highlighted. The main problems of development of the economy of common consumption, which are the threat to data security, restriction of competition, are substantiated; tax evasion, lack of social guarantees and suggested ways to solve them. To ensure the development of the economy of shared consumption, it is proposed to develop regulations, safety requirements, implement control mechanisms to ensure safety; it is proposed to introduce rules and norms of taxation, which should take into account the specifics of the economy of shared consumption. It is noted that at the state level it is necessary to promote equal conditions of competition of traditional and sharing economy taking into account the peculiarities of business models, and also substantiated the need to raise awareness about the possibilities of sharing economy, economic, environmental and social benefits.